The cost of amino acid catabolism for energy utilization in broiler chickens - Shemil P Macelline; Peter H Selle; Mehdi Toghyani; Sonia Y Liu (Poultry Science)
This review highlights that utilization of dietary amino acids for energy metabolism in broiler chickens imposes a metabolic cost, as their primary role is to support body protein synthesis. This issue becomes more critical in reduced-crude protein (CP) diets. When amino acids are used as fuel for enterocytes or undergo catabolism in the liver, they are diverted from body protein accretion. Catabolism of amino acids for energy generates α-keto acids and ammonia. α-Keto acids can be fully oxidized to produce ATP or converted into pyruvate, ketone bodies, and intermediates of the tricarboxylic acid cycle. Meanwhile, ammonia must be detoxified through the uric acid cycle, a process that requires energy, glycine, and aspartic acid. Derivatives of α-keto acids can contribute to gluconeogenesis and de novo lipogenesis, leading to glucose and fatty acid synthesis, respectively. The α-keto acid derivatives are more likely to undergo de novo lipogenesis in broilers, as evidenced by consolidated data in this review. However, de novo lipogenesis is also an energy-intensive process. Therefore, enhancing the efficiency of dietary amino acid conversion to body protein requires reducing their utilization for energy metabolism. This may be achieved through dietary manipulations, as previous studies indicate that amino acid catabolism in enterocytes and the liver is influenced by starch and protein digestive dynamics, dietary amino acid compositions, and the primary feed grain used in diets. In reduced-CP broiler diets, supplementation of glutamic acid and potentially glutamine, aspartic acid, and proline could mitigate the catabolism of essential amino acids in enterocytes. Additionally, moderating starch digestion rates may reduce amino acid catabolism in enterocytes. Moreover, optimizing the balance of dietary protein-bound and non-bound amino acids could minimize amino acid catabolism in the liver. In summary, reducing the contribution of amino acids to energy metabolism in broiler chickens is particularly beneficial in reduced-CP diets, ultimately supporting more sustainable chicken meat production.